Wynd. Book four, The power of blood - Tynion, James, IV (Boom! Box, 2025)
"As the final thrilling chapter of Wynd takes flight, the King's reign is coming to a close, with Pipetown unaware of what awaits them. Meanwhile, the Faeriekind mobilizes for war! In the face of direodds, Zedra concocts a hair-raising plan concerning her deceased brother, the Bandaged Man..."--